Stravinski in ruska glasba 20. stoletja - Savenko, Svetlana (Muzikološki zbornik, 2007)
The discussion of this important question presupposes two different aspects: the first one is connected with the perception of Stravinsky's music in his fatherland, the second with the influence of his music in the specific sense of the word. The most important stations of the perception of Stravinsky: 1. 1910-1920. Stravinsky's works were regularly performed in Russia during this period. The reaction of the audience and the press was various and partly controversial. 2. End of the 30's to the middle 1950's. In this period Stravinsky's music has almost disappeared from the USSR concert life. It became the target for most violent ideological criticism, which reached its zenith at the threshold of 1940's 1950's. 3. Stravinskys visit to the USSR (1962) had a crucial meaning for the expansion of his influence. The main factors of the influence: 1. After the 1920's the direct influence of Stravinsky on the Russian music was at first rather obvious. At that time, one could observe it through a whole set of compositions by "leftist" composersfrom the circle of The Association Of Modern Music; they understood Stravinsky's music as a renewed, contemporary musical tradition of Russia. 2. A revival of the influence of Stravinsky's music began in the 1960's, probablyin connection with "the new folkloristic wave" in the national oriented works of young composers, who belonged to a large extent to "the Soviet avant-garde". Resumé: Stravinsky's work was ideal as a model for the development of the Russian music in the 20th century.
Keywords: glasba; music; neofolklorizem; razvojni model; recepcija; sovjetska avantgarda; Stravinski, Igor, 1843-1902; vpliv